Guinea : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Waiver of Nonobservance and Modification of Performance Criterion, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Guinea's Second Review Under the Three-Year Arrangement under the Extended Credit Facility, Requests for Modifications of Performance Criteria and Waiver of Nonobservance of Performance Criterion, and Financing Assurances. Growth is projected at 4.5 percent for 2013, slightly lower than envisaged because of lower growth in the mining sector. The programs inflation target has been revised upward slightly, mainly reflecting the higher than programmed outcome at end-2012, together with some modest impact from an agreement on increases in civil service wages. Key risks include continued political unrest in the run-up to elections, which could affect growth, investment, and reform momentum, and a rebound in inflation if the private sector follows the increase in civil service wages.